2005
DOI: 10.1007/s10886-005-3544-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Antifungal and Antioxidant Activities of Acacia mangium and A. auriculiformis Heartwood Extracts

Abstract: The effect of heartwood extracts from Acacia mangium (heartrot-susceptible) and A. auriculiformis (heartrot-resistant) was examined on the growth of wood rotting fungi with in vitro assays. A. auriculiformis heartwood extracts had higher antifungal activity than A. mangium. The compounds 3,4',7,8-tetrahydroxyflavanone and teracacidin (the most abundant flavonoids in both species) showed antifungal activity. A. auriculiformis contained higher levels of these flavonoids (3.5- and 43-fold higher, respectively) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
3
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 24 publications
2
33
3
2
Order By: Relevance
“…As substâncias com núcleo fenólico apresentam destaque especial como efi cientes captadores radicalares, como demonstrado por Gyamfi et al (1999), Kujala et al (2000), Chang et al (2001), Sallem et al (2001), Thalang et al (2001, Al-Mamary et al (2002);Mihara et al (2005);Meda et al (2005);Wu et al (2005).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…As substâncias com núcleo fenólico apresentam destaque especial como efi cientes captadores radicalares, como demonstrado por Gyamfi et al (1999), Kujala et al (2000), Chang et al (2001), Sallem et al (2001), Thalang et al (2001, Al-Mamary et al (2002);Mihara et al (2005);Meda et al (2005);Wu et al (2005).…”
Section: Discussionunclassified
“…Mel obtido de A. ehrenbergina (Al-Mamary et al, 2002) e de outras espécies de Acacia (Meda et al, 2005), apresentou elevado potencial antioxidante e teor de compostos fenólicos. Extratos e compostos fl avonoídicos obtidos de A. mangium e A. auriculiformis também demonstraram intensa atividade captadora de radicais livres (Mihara et al, 2005).…”
Section: Introductionunclassified
“…While many previous studies have reported the antifungal and anti microbial activities of polyphenols of Acacia spp. bark, the precise mechanisms are not clear (Mahesh and Satish 2008;Mihara et al 2005;Mutai et al 2009). Therefore, the present study has been designed to assess the effects of various biological nitrogen supplements of several lignocellulosic materials and their combinations on the different phases of cultivation and yield of the oyster mushroom, Pleurotus ostreatus, to find the best substrate condition for efficiently increasing mushroom productivity.…”
Section: Introductionmentioning
confidence: 99%
“…Eusiderin is an example of lignan isolated from ulin (Eusideroxylon zwagery) wood (Syafii et al, 1987). Phenolic extractives of acacia induced resistance of the tree against heart wilt disease caused by fungi (Mihara et al, 2005). Scopoletin, is anti fungal compound of Hevea brasiliensis, that inhibits the spreading of Microcyclus ulei infection to other wood tissue (Jayasuriya et al, 2003).…”
Section: -165mentioning
confidence: 99%
“…Many anti fungal and anti microbial compounds were produced from plant extractives. Mechanism of extractives in inhibiting fungal growth is assumed as the result of chemicals in interfering/stalling fungal enzyme activity to decompose carbohydrate into the simplest absorbable matter for fungi digestion and metabolism (Syafii et al 1987;Jayasuriya et al, 2003;Mihara et al, 2005). As for A.crassna case here, some bioactive compounds within ethyl acetate-soluble fraction should affect F. solani fungi by inhibiting their mycelial growth.…”
Section: -165mentioning
confidence: 99%